Deregulating fixed voice services? Empirical evidence from the European Union - Amela Šaric; Mirjam R. J. Lange (International Telecommunications Society (ITS), 2014)
This paper deals with the relationship between the traditional fixed-line, mobile and Voice over IP telephony in the EU.We estimate the supply and demand for fixed-line telephony using data on 25 EU member states for the 2006:Q2 - 2011:Q4 period. Employing instrumental variable approach, we obtain the following results. First, lower prices of Voice over IP and mobile reduce the demand for fixed-line telephony. This indicates some demand-side substitution. Second, we find no relationship between Voice over IP and fixed-line prices. Third, there is a positive and significant relationship between mobile and fixed-line prices. Estimated own- and cross-price elasticities are in the inelastic range. Hence, calls to deregulate fixed-line telephony may be too premature.
Keywords: C23; L43; L51; L96; 330; Fixed networks; Mobile services; Market definition; Hypothetical monopolist test; (De)regulation